Krizni institucionalni okvir za prestrukturiranje bank in podjetij: kako naprej - Simoneti, Marko (Podjetje in delo, 2013)
The article compares new legal framework for bank rehabilitation and enterprise restructuring in Slovenia with solutions that have been used in more advanced legal systems and with those that are currently forming on the EU-level, based on experiences with the current financial crisis. Measures are proposed for better coordination between bank rehabilitation and enterprise restructuring in Slovenia and for at least partial immediate implementation of absolute priority rule, obligatory recapitalization, forced conversion (bail-ins) and going concern transactions.
Keywords: banke; ekonomska kriza; European Union; Evropska unija; podjetja; prestrukturiranje; sanacija; Slovenia; Slovenija